Multiple accretion events as a trigger for Sagittarius A* activity. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Kunneriath, D.; Czerny, B.; Karas, V.; Das, T. K.
Abstract: The Galactic center supermassive black hole is surrounded by orbiting clouds of gas. These clumps of gas may collide with each other, losing angular momentum and plunging towards the center. Observations of X-ray reflection from molecular clouds surrounding the Galactic center show evidence for enhanced activity of Sagittarius A* during the past few hundred years. These observations enable us to place constraints on the nature of past accretion events responsible for this enhanced activity. We model the source intrinsic luminosity of Sgr A* using multiple accretion events occurring at various moments in time, characterized by a range of angular momentum We also applied our scheme to the case of G2 cloud in the Galactic center.